2019
DOI: 10.5694/mja2.50218
|View full text |Cite
|
Sign up to set email alerts
|

Reduced VRE and MRSA colonisation and infection following sustained reduction in broad spectrum antibiotic use in a large tertiary hospital

Abstract: T he international shortage of piperacillin/tazobactam (PT) in 2017 prompted its replacement by intravenous amoxicillin/clavulanate (IVAC). 1 Two studies have examined the effect of broad spectrum antibiotic usage on the epidemiology of vancomycin-resistant Enterococcus (VRE) in hospitals. An interrupted time series study found that VRE prevalence declined after partial replacement of cephalosporins, vancomycin and clindamycin by ampicillin/sulbactam and, to a lesser extent, PT. 2 In another study, a switch fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A 2017 study from the John Hunter Hospital in Newcastle showed that by replacing a broad‐spectrum antibiotic with a narrow‐spectrum drug resulted in a 47% reduction in vancomycin‐resistant Enterococcus and a 42% decrease in MRSA cases respectively. Throughout this time, hand hygiene compliance was above 90% . Some of these strategies can be implemented effectively in private practice, such as encouraging participation in continuing education courses about therapeutics or conducting an audit of prescribing practice.…”
Section: Antibiotic Resistance and Dental Practicementioning
confidence: 99%
See 1 more Smart Citation
“…A 2017 study from the John Hunter Hospital in Newcastle showed that by replacing a broad‐spectrum antibiotic with a narrow‐spectrum drug resulted in a 47% reduction in vancomycin‐resistant Enterococcus and a 42% decrease in MRSA cases respectively. Throughout this time, hand hygiene compliance was above 90% . Some of these strategies can be implemented effectively in private practice, such as encouraging participation in continuing education courses about therapeutics or conducting an audit of prescribing practice.…”
Section: Antibiotic Resistance and Dental Practicementioning
confidence: 99%
“…Throughout this time, hand hygiene compliance was above 90%. 52 Some of these strategies can be implemented effectively in private practice, such as encouraging participation in continuing education courses about therapeutics or conducting an audit of prescribing practice. Three audit cycles conducted over 3 years at a British emergency dental service found that by reinforcing correct documentation (e.g.…”
Section: Antibiotic Resistance and Dental Practicementioning
confidence: 99%
“…Antimicrobial resistance manifests itself through the development of multiresistant organisms such as vancomycin‐resistant Enterococcus (VRE) and methicillin‐resistant Staphylococcus aureus (MRSA) species. For example, it is well established that the use of broad‐spectrum antibiotics such as piperacillin–tazobactam is associated with an increase in hospital‐onset VRE and MRSA infections 3 . Antimicrobial resistance not only delays recovery and prolongs hospital stay but also associated with increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is well established that the use of broad-spectrum antibiotics such as piperacillin-tazobactam is associated with an increase in hospital-onset VRE and MRSA infections. 3 Antimicrobial resistance not only delays recovery and prolongs hospital stay but also associated with increased mortality. It is estimated that there are 290 deaths annually from antimicrobial-resistant bacteria in Australia.…”
mentioning
confidence: 99%
“…A unit’s ecology can change over a relatively short period of time 4. We know for example that units that use ampicillin and gentamicin have lower AMR rates than those that use a third-generation cephalosporin,5 and a recent study showed where piperacillin-tazobactam became unavailable the resistance rates fell over months 6…”
mentioning
confidence: 99%